Protocol for the Yapatjarrathati project: a mixed-method implementation trial of a tiered assessment process for identifying fetal alcohol spectrum disorders in a remote Australian community - Shanley, Dianne C; Hawkins, Erinn; Page, Marjad; Shelton, Doug; Liu, Wei; Webster, Heidi; Moritz, Karen M; Barry, Linda; Ziviani, Jenny; Morrissey, Shirley; O'Callaghan, Frances; Wood, Andrew; et al. (BMC Health Services Research, 2019)
Fetal alcohol spectrum disorder (FASD) is a highly prevalent neurodevelopmental disorder associated with prenatal alcohol exposure. Early identification can improve functioning for individuals and reduce costs to society. Gold standard methods of diagnosing FASD rely on specialists to deliver intensive, multidisciplinary assessments. While comprehensive, prevalence rates highlight that this assessment model cannot meet demand, nor is it feasible in remote areas where specialist services are lacking. This project aims to expand the capabilities of remote practitioners in north Queensland, Australia, where 23–94% of the community identify as First Nations people. Integrating cultural protocols with the implementation science theories of Knowledge-To-Action, Experience-Based Co-Design, and RE-AIM, remote practitioners with varying levels of experience will be trained in a co-designed, culturally appropriate, tiered neurodevelopmental assessment process that considers FASD as a potential outcome. This innovative assessment process can be shared between primary and tertiary health care settings, improving access to services for children and families. This project aims to demonstrate that neurodevelopmental assessments can be integrated seamlessly with established community practices and sustained through evidence-based workforce development strategies.